Human Mobility Datasets in the Complex Metro System of Shanghai - Peiyan Sun (20877737) (2025)
MetroFlow is an open-sourced, city-scale metro flow dataset, covering the period of May-August 2017 and 302 metro stations in Shanghai, China. This repository contains five csv files: - Station Attributes Data (stationInfo.csv) - Metro Station Inflow and Outflow Data (metroData_InOutFlow.csv) - Metro Station Origin-Destination Flow Data (metroData_ODFlow.csv) - Meta Data (shanghai_weatherHourly.csv, work_calendar.csv) The Jupyter notebooks used for dataset organization and analysis in this project are available as open-source resources at https://github.com/Ariza-Sun/MetroFlow.